(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The most frequent and beneficial uses of nanotechnology in terms of civil engineering, is the use of it in concrete. Furthermore, it has been observed that better understanding and engineering of complex structures made by cement, steel or composite materials at nano-level will definitely result in a new generation of construction materials with higher performance in strength, durability, and other properties The paper also includes applications and properties with which construction materials could be more affective, durable and high performing by using nano-materials. The smart designs and planning, construction projects can be made sustainable and avoid damage to environment. Nanotechnology offers opportunity to develop sustainable, light weight concrete structure for different adverse environments reducing energy consumption during cement production.